Ancestry-Based Intracategorical Injustices in Carcinogenic Air Pollution Exposures in the United States. Issue 8 (2nd August 2020) - Rubio, Ricardo; Grineski, Sara; Collins, Timothy; Morales, Danielle X.
Abstract: Previous studies of US environmental inequalities have focused on racial/ethnic differences in air pollutant exposure. Few have applied an intracategorical framework, which enables the identification of within-group differences through the examination of subgroups. We applied this framework to examine exposure disparities between 26 ancestry/ethnic origin groups within five US racial/ethnic categories. Data came from the US Census, American Community Survey, and National Air Toxics Assessment. We calculated national population-weighted lifetime cancer risk (LCR) scores from residential exposure to hazardous air pollutants. Results showed that Americans of Dominican, Ethiopian, and Somalian descent have the highest total LCR scores at 53.1, 49.2, and 48.3 estimated excess cases of cancer per one million people, respectively. Use of the intracategorical framework enabled characterization of disparate risks that would be overlooked based on the conventional assumption that racial/ethnic environmental inequalities conform to broad, homogenous categories. Intracategorical studies can inform interventions by identifying environmentally-disadvantaged socio-demographic groups.